2014
DOI: 10.5194/angeo-32-651-2014
|View full text |Cite
|
Sign up to set email alerts
|

Mirror mode structures near Venus and Comet P/Halley

Abstract: Abstract.In this paper, we study where mirror mode structures are generated near unmagnetized solar system bodies (Venus and comet P/Halley measured in situ by Venus Express and Giotto). To estimate the location of the mirror mode source region at Venus, we apply a turbulent diffusion model of mirror mode structures, which has already been successfully tested in planetary magnetosheaths (Earth, Jupiter, Saturn). It enables us to estimate the distance between the measured location of the mirror mode and the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 27 publications
(37 reference statements)
10
45
0
Order By: Relevance
“…For water ions at a magnetic field strength of B m ≈ 20 nT this leads to T mm ≈ 9 α s. With the measured T mm mentioned above this leads to 11 ≤ α ≤ 16, which is similar to what was found by Tsurutani et al (1999) at comet 21P/Giacobini-Zinner, α GZ ≈ 12, but much larger than what was found by Schmid et al (2014) at comet 1P/Halley, α H ≈ 1-2. Taking the ion velocity as measured by IES, the Larmor radius for water ions becomes ρ H 2 O, i ≈ 280 km.…”
Section: Crossing From 6 To 7 June: Mirror-mode Wavessupporting
confidence: 84%
See 2 more Smart Citations
“…For water ions at a magnetic field strength of B m ≈ 20 nT this leads to T mm ≈ 9 α s. With the measured T mm mentioned above this leads to 11 ≤ α ≤ 16, which is similar to what was found by Tsurutani et al (1999) at comet 21P/Giacobini-Zinner, α GZ ≈ 12, but much larger than what was found by Schmid et al (2014) at comet 1P/Halley, α H ≈ 1-2. Taking the ion velocity as measured by IES, the Larmor radius for water ions becomes ρ H 2 O, i ≈ 280 km.…”
Section: Crossing From 6 To 7 June: Mirror-mode Wavessupporting
confidence: 84%
“…at comet 1P/Halley (see e.g. Schmid et al, 2014;Volwerk et al, 2014). The instability criterion for MM waves is given by:…”
Section: Crossing From 6 To 7 June: Mirror-mode Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The shock compression has been argued to be a source of free energy that generates peak-like MMs and likely both sources need to be available in order to generate the largest amplitude MMs (Tsurutani et al, 2011b). In the heliosheath and cometosheaths, the ion pickup process is also identified as a free energy source (e.g., Tsurutani et al, 1999Tsurutani et al, , 2011aSchmid et al, 2014).…”
Section: M Ala-lahti Et Al: Mirror Mode Wave Occurrence In Icme-mentioning
confidence: 99%
“…They are frequently observed in heliospheric plasma, in particular in different sheath structures. They are the most widely studied in the planetary magnetosheaths (e.g., Tsurutani et al, 1982;Hellinger et al, 2003;Soucek et al, 2008Soucek et al, , 2015Volwerk et al, 2008;Génot et al, 2009b;Herčík et al, 2013;Schmid et al, 2014;Volwerk et al, 2016), but also found in cometosheaths (e.g., Russell et al, 1991;Glassmeier et al, 1993;Tsurutani et al, 1999;Schmid et al, 2014), in the heliosheath (e.g., Liu et al, 2007;Génot, 2008;Tsurutani et al, 2011a) and ahead of the dipolarization front (Wang et al, 2016). MMs are also studied in the solar wind (e.g., Hellinger et al, 2006Hellinger et al, , 2017Bale et al, 2009;Russell et al, 2009), behind interplanetary shocks ) and in addition in interplanetary coronal mass ejections (ICMEs; Siu-Tapia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%